Information System for the Inventory of Census Needs at the Central Statistics Agency of Sragen Regency: Sistem Informasi Inventaris Keperluan Sensus Badan Pusat Statistik Kabupaten Sragen - Hajid, Luthfi Hayban; Naury, Chairullah; Purbiyanto, Eko (Politeknik Harapan Bangsa Surakarta, 2024)
The inventory system is a system used to input inventory data into a database to avoid errors in entering, retrieving, and losing inventory data. The limitation of manual inventory recording for census purposes at the Central Statistics Agency (Badan Pusat Statistik) in Sragen Regency causes a relatively long reporting time for inventory and the possibility of errors in data collection. To support the performance of employees, a computerized system is needed as a tool for employees to carry out their activities. Considering the increasing amount of inventory data that needs to be stored at the Central Statistics Agency in Sragen Regency, there is a need for a web-based inventory information system for census purposes. The aim of this research is to design an inventory information system for the needs of the census at the Central Statistics Agency in Sragen Regency. The author uses the Waterfall method in the system development process and the PHP programming language, along with the MySQL database. The system designed by the author is expected to produce an application that can record inventory accessible via the web so that the leadership can directly see the inventory at the Central Statistics Agency in Sragen Regency.